Teachers at Bulukumba State Special Needs School 1's Strategies for Dealing with Meltdowns in Autistic Children Aged 5-8 Years - Ardillah; Alfina; Hawa; Siti Nurhalizah; Andi Nidha Eka Restuti Munawir (Aksiologi : Jurnal Pendidikan dan Ilmu Sosial, 2025)
Meltdown in children with autism refers to a condition in which the child loses emotional control due to sensory overload, changes in routine, or difficulty expressing needs. This phenomenon frequently occurs in special education settings, including at SLB Negeri 1 Bulukumba, particularly among children aged 5–8 years. This study aims to describe the strategies used by teachers to manage meltdowns and identify factors that influence their effectiveness. This research employed a qualitative approach with a case study design. The participants consisted of one classroom teacher selected through purposive sampling. Data were collected through observation, in-depth interviews, and document analysis over two days (9–10 November 2024), and were analyzed using the Miles, Huberman, and Saldaña interactive model. The findings reveal three main strategies: preventive strategies, including building emotional rapport, adjusting learning activities to students' interests, and strengthening routines; intervention strategies, involving maintaining a calm atmosphere, reducing stimulation, and providing safe physical contact; and post-meltdown recovery strategies, including allowing emotional cooldown time, assigning light activities, and evaluating triggers to adjust individual learning plans. The effectiveness of these strategies is shaped by classroom conditions, overstimulation risks, available facilities, and communication with parents. This study highlights the importance of empathetic, flexible, and context-sensitive approaches in supporting emotional regulation for children with autism in special education settings.